Distribution Characteristics and Influencing Factors of Central Apnea in Chinese Pediatric Patients With Obstructive Sleep Apnea: A Single-Center Study - Liu, Jing; Chang, Li; Cao, Ling; Huang, Guimin (Frontiers in Pediatrics, 2022)
Background: Central apnea(CA) events always can be seen in the polysomnographic (PSG) reports of children with obstructive sleep apnea (OSA), and sometimes the central apnea index (CAI) is higher than the obstructive apnea and hypopnea index (OAHI). Commonly, the clinicians only attribute it to the age. This study aims to elucidate the distribution characteristics and major factors associated with CA in pediatric OSA. Methods: A retrospective chart review of PSG data of children with OSA from January 2017 to March 2018 was performed. Results: 856 children (317 girls and 539 boys, 4.9±2.4 years) were involved. 50.1% (429/856) had a CAI >1, and 2.9% (25/856) had a CAI >5. Children with a CAI >1 had a higher OAHI, arousal index(AI), oxygen desaturation index(ODI), and a longer REM period, but a younger age and a shorter slow-wave sleep(SWS) phase. Multivariate binary logistic regression showed that with a 1% increased REM period, the risk of the CAI being >1 increased by 5.3% (p＜0.001). The CAI increased with an increasing OAHI (p=0.003). The possibility of a CAI ≤1 increased with age (p＜0.001), and boys were more likely to have a CAI ≤1 (p=0.001). Conclusions: In addition to obstructive apnea (OA), almost all children with OSA also had CA, and a CAI >1 was most likely to occur. The OAHI and REM period were risk factors for an increased CAI, and age and male sex were protective factors.